Arm's-Length Trade : A Source of Post-Crisis Trade Weakness - Lakatos, Csilla (World Bank, Washington, DC, 2017)
Trade growth has slowed sharply since the global financial crisis. U.S. trade data highlights that arm's-length trade —trade between unaffiliated firms—accounts disproportionately for the overall post-crisis trade slowdown. This is partly because arm's-length trade depends more heavily than intra-firm trade on emerging market and developing economies (EMDEs), where output growth has slowed sharply from elevated pre-crisis rates, and on sectors with rapid pre-crisis growth that boosted arm's-length trade pre-crisis but that have languished post-crisis. Compounding such compositional effects, arm's-length trade is also more sensitive to changes in demand and real exchange rates. For example, the income elasticity of arm's-length exports is about one-fifth higher than that of intra-firm exports. Hence, post-crisis global growth weakness has weighed more on arm's-length trade than on intra-firm trade. Unaffiliated firms may also have been hindered more than multinational firms by constrained access to finance during the crisis, heightened policy uncertainty, and their typical firm-level characteristics.